KEPEMIMPINAN TRANSFORMASIONAL DALAM TINJAUAN SEJARAH DAN PERKEMBANGAN KAJIANNYA PADA BIDANG PENDIDIKAN - Nasukah, Binti; Maunah, Binti (STKIP Pesisir Selatan, 2021)
Transformational leadership is becoming the popular concepts in the management science for the last30 years, as well as in the field of education management. To avoid an application in the educationsector that is merely followed because of trending, it needs an understanding of the historical side ofthe transformational leadership model. Through the literature study, this study presented threethings: (1) The history of the development of leadership theories; (2) The history of atransformational leadership theory model, and (3) the development of transformational leadershipstudies in the field of education. The development of leadership studies involving intrinsic andextrinsic motivational theories, has spawned the idea of an intrinsic transformational leadership,compared to extrinsic transactional leadership. Inspired by the writings of James McGregor Burns(1978), Bernard M. Bass (1990) created the concept of transformational leadership model, to popularand became an important study to be implemented in various sectors, including in the field ofeducation. The study of transformational leadership in the area of pedagogy has come to theconclusion that transformational leadership is an ideal representation of the practice at school in the21st century.